Analysis and forecast of road traffic accident in Saudi Arabia from 1990 until 2018 - Abouammoh, Nada A.; AlRuwais, Norah A.; Abouammoh, Noura A. (International Journal Of Community Medicine And Public Health, 2021)
Background: Road traffic accidents (RTAs) are an epidemic problem in Saudi Arabia, resulting in high morbidity and mortality rates. This paper investigates the increasing number of RTAs and their related injuries and mortalities in Saudi Arabia. Methods: This study was performed on the population of Saudi Arabia using secondary data from the general authority for statistics from 1990 to 2018. Correlation among the variables (RTAs, injuries, mortalities, and population) was conducted using statistical package for the social sciences (SPSS), and forecasts of their trends over the next ten years using linear regression was discussed. Results: Eastern, Makkah and Riyadh regions were the top three regions in the number of RTAs accounting for 69% of the total RTAs in Saudi Arabia. All regions have had a pattern of RTA rise from 1990 till 2014 that dropped in the last 4 years. Riyadh had the highest injury rate per 10,000 RTA, although it had the lowest RTA rate per 100,000 population in the period from 2010-2014. Mortality rate in Riyadh doubled between the years 2014 and 2018 while Makkah accounted for the highest RTA-related mortality rates. The correlation between RTAs and mortalities were the highest in the country (r=0.92). In 2030, the average annual increase in the rate of RTAs, related injuries, and related mortalities will be 3%, 2% and 2.1%, respectively. Conclusions: Decision makers in Saudi traffic and transportation department should continue monitoring accidents prevention strategies and their effect. Reasons behind high injury and mortality rates, despite the decrease in the rate of RTAs, should be investigated.